Dakwah Media Sosial Gus Baha dan Relevansinya dalam Kehidupan Sosial Kontemporer - Khafidhoh, khafidhoh (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article attempts to explore social values originating from the hadiths conveyed in Gus Baha's lectures and their relevance in contemporary life. Research on the relevance of hadith as a basis for social values in contemporary life is important because the distance between the narration of the Prophet's hadith and today's life is not short, while human problems are increasingly developing, especially due to the rapid influence of digital technology. This research uses a qualitative approach with netnographic methods. Primary data comes from Gus Baha's lectures uploaded on social media. Meanwhile, secondary data comes from books, articles and information from online media that are appropriate to the discussion. The findings from this research are that social values originating from the hadith of the Prophet quoted in Gus Baha's lecture include 3 values, namely 1) Loves (compassion), which includes a forgiving attitude and being good at measuring attitudes (muhasabah). 2) Responsibility (responsibility) which includes an attitude of responsibility. 3) Life harmony (life harmony) which includes an attitude of tolerance and maintaining good relationships with other people (maintaining friendship). The hadiths in Gus Baha's lecture are quite relevant to the problems that exist in contemporary life